Left unilateral scrotoschisis in a newborn referred after vaginal delivery in midwife practice in a State Hospital in Medan, Indonesia - Erjan Fikri; Fini Meirisa Alnaz; Ahmad Razi Maulana Alnaz; Nurdiani (Elsevier, 2023)
Scrotoschisis is an uncommon congenital urogenital anomaly with a defect in the scrotum causing protrusion of testis through the scrotal wall. This is the 20th case reported and 1st from Indonesia. A male newborn admitted with a complaint mass protruding from his left hemiscrotum. Mass was described with spherical shaped, red base, yellowish membrane, smooth and firm boundaries with no sign of testicular torsion. Patient was diagnosed with left unilateral scrotoschisis. Patient was managed with surgical debridement, scrotal exploration and orchidopexy. The patient was managed with drain insertion to monitor signs of infections. Patient was stable and discharged, hence testicular function monitoring was planned in line with further growth assessment.